Proses Inovasi Teknologi EFT •(Electric Fuel Treatment) Penghemat BBM Kendaraan Bermotor Kasus: UPT Balai Pengembangan Instrumentasi Lipi Bandung (UPT BPI Lipi Bandung) - Murwanto, Tri Agus (Warta Penelitian Perhubungan, 2011)
The success of an organization depends to human and science which is had, because science was felt more precious than nature resources, modem machine or much money. Innauation organization will working with new innauation ways, which changes old ways for restrain growth of curve through renew technology, if technology do not renewed the growth will be stuck or even going down. Therefore, research and development departement which was knew as the institution is full fill research and technology, it should be the main role to increase of growing of science and technology in the future time.Key words: Innauation, process of technology EFT